Status Kepemilikan Tanah Adat Yang Didaftarkan Secara Sporadik Di Kota Tual - Ari Sadewo; Sri Susyanti Nur; Muhammad Ilham Arisaputra (Widya Yuridika, 2022)
The Land Registration System according to Government Regulation Number 24 of 1997 does not include Customary/Ulayat Land as the subject of registration, but the Southeast Maluku Land Office registers customary lands sporadically through the First Registration mechanism, then the Tual City Government recognizes Larvul Ngabal as a customary law system by issuing a City Regulation Tual Number 04 of 2020 concerning Ratschap, Ohoi/Finua which was submitted to the Land Office of Southeast Maluku Regency is currently only owned by individuals/individual clans, with the stipulation that the conversion/proof of old rights is processed through the Recognition of Rights and the legal status changes from former land Customary rights become property rights that have legal force in accordance with the provisions of the legislation of the Unitary State of the Republic of Indonesia.